Unravelling microstructure of novel as-cast in-situ α Ti and β Ti-Nb alloy matrix composites with NbC addition - Manso Gonçalves, Vinícius Richieri [UNESP]; Lisboa Filho, Paulo Noronha [UNESP]; Moreira Afonso, Conrado Ramos (Elsevier, 2023)
The NbC powder was added to commercially pure Ti and β Ti-40Nb alloy and prepared by an arc-melting process, and its effect on the as-cast samples was microstructurally investigated with electron backscattered diffraction (EBSD). The results showed that two in-situ Ti-based matrix composites (TMCs) were produced due to chemical reactions during melting. In summary, each TMC presented only two phases: α Ti matrix reinforced with TiC phase (in the case of Ti + 5 %NbC), and β Ti-Nb matrix reinforced with TiC (in the case of Ti-40Nb + 5 %NbC). Furthermore, the results showed that the composite composition affects the TiC morphology, such as a short rod shape was obtained with richer Ti content in the Ti:C fraction (Ti + 5 %NbC), whereas lowering the Ti proportion (Ti-40Nb + 5 %NbC) resulted in equiaxed granular TiC. Thus, this study provides additional microstructural information about promisors wear-resistant TMCs.
Keywords: Arc-melting; EBSD; In-situ TiC; Metal matrix composites; β Ti-Nb alloys